Determinant of Car Demand in Java Island - Dyah Candra Kirana; Prasetyo Ari Bowo (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The purpose of this research is to examine factors that affect car demand in Java Island in 2012-2016. The research method used in this research is panel least square The data used in this research is panel data. The panel data consists of time series data (2012-2106) and cross section data (six province in Java Island, those are DKI Jakarta, Jawa Barat, Jawa Tengah, DI Yogyakarta, Jawa Timur, and Banten). Data were obtained from Central Bureau of Statistic Republic of Indonesia (BPS). Data analysis used is panel data analysis. The results showed that income per capita, population, and inflation have simultan effect on car demand in Java Island in 2012-2016. Per capita income has a positive and significant effect on car demand in Java Island in 2012-2016. Population has a positive and significant effect on car demand in Java Island in 2012-2016. Inflation has positive and insignificant effect on car demand in Java Island in 2012-2016.